Reconsidering Inuit presence in southern Labrador - Stopp, Marianne (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2002)
AbstractThis paper reconsiders the century-old question of Inuit presence south of Hamilton Inlet and the contention that it was a short-term presence for the purpose of trading with Europeans. A summary of archival sources largely unavailable in English in conjunction with known and previously unreported archaeological evidence are the basis for a reexamination of the nature and extent of Inuit presence in the southern region. A discussion of the Inuit hunting and gathering way of life alongside the archival and archaeological evidence suggests that there is reasonable evidence of winter and summer presence, of family groups rather than trade parties, of extended habitation rather than short-term trade forays, and of a way of life that incorporated European goods but remained based on traditional seasonal foraging patterns. This update, whilst incorporating previously unpublished archaeological data for the region between Blanc Sablon and Sandwich Bay, supports the original contention presented in Martijn and Clermont, eds (1980) that Inuit did inhabit the southern region prior to the late eighteenth century.